Seeing justice done: Courtroom filming and the deceptions of transparency - Moore, Sarah (Crime, media, culture, 2021)
There has been a global shift towards courtroom broadcasting in a bid to extend the public gallery into a virtual realm. Such initiatives tend to be based on the idea that transmitting the courtroom boosts transparency and with it public trust in criminal justice. This is an untested ambition. Moreover, the idea that filming opens a window onto the courtroom comes up against the reality that any transmission entails translation, involving choices and compromises. Based on an in-depth study of courtroom filming and audience response, this article identifies two globally dominant stylistic modes and analyses their meaning and reception. We found that different stylistic modes prompt different types of audience engagement and allow for different levels of comprehension. The analysis therefore provides an insight into how courtroom footage is consumed by the viewing public. It also contributes to our understanding of the norms and values of institutional transparency.